Traumatic brain injury and neuropsychiatric complications - Saeed Ahmed (Indian Journal of Psychological Medicine, 2017)
Traumatic brain injury (TBI) occurs when a blow or jolt to the head or a penetrating injury results in damage to the brain. It is the most frequent cause of hospitalization in young people with a higher prevalence in men. TBI is the leading cause of disability and mortality between the ages 1 and 45. TBI can be caused either by the direct result of trauma or due to a complication of the primary injury. The most common etiological factors for TBI are falls, road traffic accidents, violent physical assaults, and injuries associated with athletic activities. Following TBI, significant neurologic complications may occur which include seizures, dementia, Alzheimer's disease, and cranial nerve injuries. In addition, people may suffer from various psychiatric complications such as depression, posttraumatic stress disorder, generalized anxiety disorder, obsessive-compulsive disorder, and other cognitive and behavioral sequel that might significantly increase the comorbidity of the victims. Considering all of the above complications, TBI is one of the significant public health burdens. Literature has shown that only about 25% of people achieve long-term functional independence following TBI. In this paper, we focused not only on the epidemiology but also the etiology, complications following TBI and understanding their underlying pathogenesis. Further, we focused on analyzing the options to improve the treatment and rehabilitation following TBI in future.